LEGAL REGULATION ABOUT THE USE OF HALAL LABEL TO PROVIDE MUSLIM CONSUMERS PROTECTION - Supaino, Edy; Roestamy, Martin (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2017)
Perpetrators of the restaurant business should provide protection to consumers of food that will be consumed, the more this problem becomes a very important problem in the midst of rapid food technology, that is food business actors are not transparent with Muslim consumers. The identification of this research includes: (1) how the use of halal labels by industry and restaurants;, (2) legal protection for Muslim consumers against halal labeled foods, legal efforts against the misuse of halal labels (3). The research method used in this research is the normative juridical approach. The results of this research are: (1) Implementation of halal label with the process of obtaining halal certification for restaurant done by restaurant x has been in accordance with the requirements of halal certification HAS 23000 from LPPOM-MUI.; (2) Provisions of halal products have been regulated in the legislation between other laws concerning: consumer, food, assurance of halal products. The provisions of the regulation are manifestations of universal Islamic legal values that must be supported by their execution; (3) There are 2 (two) dispute settlements that can be taken by the consumer, namely the first settlement of disputes outside the court that is with conciliation, mediation, and arbitration, through the Agency of Consumer Dispute Settlement Agency and both dispute settlement in court.Keywords: Rule of Law, Halal Label, Consumer Protection for Muslims